Chapter 11 "That in the Reducciones Had Been Noise of Weapons . . ." The Introduction of Firearms in the Seventeenth-Century Jesuit Missions of Paraguay - Svriz-Wucherer, Omar (Taylor & Francis, 2021)
history of the Americas